Entropy production due to free convection in partially heated isosceles triangular enclosures - Varol, Yasin; Öztop, Hakan Fehmi; Koca, Ahmet (Pergamon-Elsevier Science Ltd, 2008)
A numerical analysis of the entropy production has been performed due to natural convection heat transfer and fluid flow in isosceles triangular enclosures with partially heated from below and symmetrically cooled from sloping walls. Governing equations are solved by finite difference method. Governing parameters on flow and temperature fields are Rayleigh number (10(3) <= Ra <= 8.8 X 10(5)), dimensionless length of heater (0.25 <= (l' = l/L) <= 1.0), dimensionless location of heater (0.25 <= (c' = c/L) <= 0.75) and inclination angle of slopping walls (30 degrees <= beta <= 60 degrees). Heat transfer results are presented in terms of local and mean Nusselt numbers (Nu) while entropy production results are shown with entropy production number (N-s) and Bejan number (Be). Isotherms, streamlines, contours of entropy production due to heat transfer and fluid friction irreversibility are plotted. It is observed that entropy production number increases but Bejan number decreases with increasing of Rayleigh number. However, both entropy production due to heat transfer and fluid friction irreversibility are affected by higher inclination angle of triangle and length of heater. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: natural convection; entropy; isosceles; triangular cavities